Studi Perilaku Makan dan Analisis Vegetasi Pakan Lutung Jawa (Trachypithecus Auratus) di Taman Nasional Gunung Ciremai - Iqbal Amiruddin Ihsanu; Agus Setiawan; Elly Lestari Rustiati (Jurnal Sylva Lestari, 2013)
Javanmonkey (Trachypithecus auratus) an endemic primate of Java is vulnerable and listed in Appendix II of CITES. This study was done to observeits feeding behavior and food diversity. The results is expected to support its population in the wild from the destruction of habitat. It was conducted in March-April 2012 in Situ Sangiang Gunung Ciremai National Park, Majalengka, West Java Province. The method used is animal scan sampling was applied feeding behavior and purposive sampling to determine the vegetation diversity. Its feeding monkey between 07:00 to 11:00; 13:00 to 14:00; and 15:00 to 17:00 time in tree stratum (> 15 meters), mostly on haripingku (Dysoxylum densiflorum). Other food plant shantap (Sterculia oblongata), kigambir (Uncaria gambir), nangsi (Villebrunea rubescens), kiara (Ficus globosa), hamirung (Vernonea arborea), mara (Macaranga tanarius), tisuk (Hibiscus macrophyllus), kiara koneng (Ficus annulata Bl.), mahoni (Swietenia mahagoni), saninten (Castanopsis argentea), and nunuk (* not identified). Keywords: feeding behavior, Gunung Ciremai National Park, Javan monkey